Evaluation of the impact of heat stress at flowering on spikelet fertility and grain quality in barley - Camilla Beate Hill; Tefera Tolera Angessa; Sharon Westcott; Lee-Anne McFawn; Hamid Shirdelmoghanloo; Yong Han; Chengdao Li (Agriculture Communications)
Against the backdrop of a warming climate, heat stress has become one of the most limiting factors to crop productivity and food security worldwide. The flowering stage is susceptible to high temperatures in cereal crops, leading to severe grain yield losses by decreasing fertility and seed-setting rate. Our objective was to (1) assess a global panel of 572 barley varieties with contrasting genetic backgrounds for various agronomic traits related to spikelet fertility and grain quality, (2) identify barley germplasm with superior spikelet fertility and seed set under extreme heat conditions, and (3) understand the relationship between spikelet fertility and grain quality traits under heat stress at flowering time. Delayed sowing in target field environments as well as combined birdcage and heat chamber experiments were conducted in Western Australia for two consecutive years. Twenty-one agronomic traits, including spikelet fertility, grain plumpness, thousand-kernel weight, and screenings, were assessed when heat stress occurred during the crucial flowering period. Our study showed that varieties that flowered during heat stress periods recorded an average of 5–20 ​% lower spikelet fertility than those flowered outside the stress windows. Varieties with high or reduced spikelet fertility under heat stress were identified in the barley panel and showed significant differences of more than 80 ​% in Australian varieties. Based on decreased spikelet fertility, several research lines, but only a few cultivars, maintain spikelet fertility after heat stress compared to control conditions, providing evidence of adaptation to high temperatures in some genotypes. Our study shows that spikelet fertility at high temperatures is a valuable screening tool for heat tolerance during the reproductive phase. Information on heat-tolerant and susceptible varieties can improve the spikelet fertility of the next generation of barley cultivars and enhance adaptation to a changing climate.